Perioral dermatitis from high fluoride dentifrice: a case report and review of literature. (27th August 2013) - Peters, P; Drummond, C
Abstract: Perioral dermatitis is a papulopustular eruption, commonly related to the inappropriate application of topical corticosteroids with occasional reports of inhaled corticosteroids and decreased personal hygiene. We present a case of a 45‐year‐old female with a one‐year history of perioral dermatitis related to the use of highly fluoridated toothpaste commenced to control dental caries.